2019
DOI: 10.1590/1678-4162-10098
|View full text |Cite
|
Sign up to set email alerts
|

Perfil metabólico de vacas Holandês e mestiças Holandês x Jersey no periparto

Abstract: RESUMO O objetivo do presente trabalho foi determinar e comparar o perfil metabólico de vacas Holandês (H) e mestiças Holandês x Jersey (HxJ) no periparto. Avaliaram-se 24 vacas, sendo 11 vacas Holandês e 13 mestiças Holandês x Jersey. Semanalmente, coletou-se sangue para a determinação das concentrações séricas de glicose, beta-hidroxibutirato (BHB), proteína total, albumina, aspartato aminotransferase (AST), creatinoquinase (CK), cálcio total, cálcio iônico, magnésio, fósforo inorgânico e colesterol. Avaliou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…This observation agrees with other studies which compare the glucose levels of Holstein and crossbred cows. Pellizza et al [ 33 ] reported no difference in glucose levels by comparing Holstein and crossbred Holstein × Jersey cows. Glucose records ranged between 59 and 63 (mg/dl) for both genetic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation agrees with other studies which compare the glucose levels of Holstein and crossbred cows. Pellizza et al [ 33 ] reported no difference in glucose levels by comparing Holstein and crossbred Holstein × Jersey cows. Glucose records ranged between 59 and 63 (mg/dl) for both genetic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies evaluating the transition period of dairy cows were performed with the Holstein breed [ 29 , 30 , 31 ]. A number of studies evaluated Holstein × Montbeliarde, Holstein × Jersey or Holstein × Simmental crossbred cows in comparison with one of the parental breeds (most often Holstein) [ 4 , 32 , 33 , 34 ]. Only a very few studies compared crossbred Holstein × Simmental cows and both parental breeds [ 12 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…A treatment with 5-hydroxytryptophan (the immediate precursor to serotonin synthesis) could actually decrease the BHB concentration at days 6-10 postpartum, what might lead to a more stable energy homeostasis, particularly in Jersey cows (Weaver et al 2017). By comparing Holstein with crossbred Holstein x Jersey cows at two weeks before and eight weeks after calving, Pelizza et al (2019) did, however, not find any difference between the breeds for BHB. They reported a difference between transition periods with higher BHB values after calving.…”
Section: Discussionmentioning
confidence: 88%
“…Block e Litherland (2013), a dieta aniônica é uma forma de se evitar a hipocalcemia clínica e subclínica. Animais que apresentam hipocalcemia subclínica tendem a ficar mais susceptíveis a doenças, como febre, metrite, retenção de placenta, além de redução da função de células (PELIZZA et al, 2019). O fornecimento de dietas aniônicas 30 dias no pré-parto evita falhas na homeostase de cálcio e no pós-parto previne quadros de hipocalcemia (SEIFI et al, 2010).…”
Section: Resultsunclassified